PENGEMBANGAN LKPD BERBASIS DEEP LEARNING UNTUK MENINGKATKAN LITERASI DAN HASIL BELAJAR SISWA PADA MATERI PEMANFAATAN DAN PELESTARIAN SUMBER DAYA ALAM DI KELAS VIII SMPN 1 MODO LAMONGAN - mutitah, mutitah; Sigit widodo, Bambang; Fahrudin Fadirubun, Fahmi (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2026)
Abstract: This study aims to develop a deep learning-based Student Worksheet (LKPD) to improve students' literacy and learning outcomes on the topic of natural resource utilization and conservation in grade VIII at SMPN 1 Modo Lamongan. This development research uses the ADDIE model with a quasi-experimental non-equivalent control group design. The research subjects were 54 grade VIII students divided into an experimental group (27 students) and a control group (27 students). Research instruments included validation sheets, pretest-posttest questions, literacy observation sheets, and student response questionnaires. The results show: (1) the deep learning-based LKPD is highly suitable for use with an average validation score of 91.97%; (2) students' literacy skills increased significantly with 70.4% of students reaching the high category in the third meeting; (3) learning outcomes of the experimental class increased by 27.41 points (classical completeness 88.9%) compared to the control class which only increased by 15.55 points (classical completeness 59.3%) with p-value 0.000 < 0.05; and (4) student responses were very positive with an average of 95.9%. This study proves that deep learning-based LKPD effectively improves students' literacy and social studies learning outcomes through mindful, meaningful, and joyful learning in accordance with the deep learning principles of the Merdeka Curriculum. Keywords: Student Worksheet, deep learning, literacy, learning outcomes, natural resources